Analisis Pengembangan Electronic Government Melalui Penyelenggaraan Website Di Pemerintahan Daerah Kabupaten Padang Pariaman - Eka Rolania Batubara; Herlina Helmy (Universitas Negeri Padang, 2019)
This study aims to further examine how the development of e-government in government institutions and what obstacles are faced in implementing e-government. This research uses interpretive qualitative. The process of this research is interactive and means that is not measured based on statistical data and the aim is to explore various information obtained in more depth and to get things implied by the data collection conducted in triangulation. This data analysis is inductive and the results of qualitative research emphasize the meaning of generalization. This interpretive research method seeks to formulate a question then be analyzed based on the perception questions of the participants studied. The research was conducted in one of the government agencies namely the Office of Communication and Information in Padang Pariaman Regency. To find out the extent of e-government development in Padang Pariaman Regency in this study using the results of studies and research from the Hardvard JFK School of Government, the elements of success which include support, capacity and value. The results of the study can be found that the development of e-government in Padang Pariaman is still not optimal. The development of e-government in Padang Pariaman Regency is also still hampered by several factors such as the lack of strong political will, the lack of availability of human resources and infrastructure as well as the lack of budget from the government so that the government of Padang Pariaman Regency needs to increase human resources and infrastructure to support the success of e-development government in Padang Pariaman Regency.